Analisis Segmentasi Pasien Pelayanan Kesehatan di Instalasi Rawat Jalan RSUD Kabupaten Mamuju (Window of Public Health Journal, 2026)
The growing number of hospitals in Indonesia has led to fiercer competition in the provision of healthcare services. To maintain and improve patient loyalty, hospitals need to understand patient characteristics through market segmentation. This study aims to determine the segmentation of patients using healthcare services at the Mamuju Regency Regional General Hospital in the outpatient setting based on market segmentation characteristics. This study is quantitative, with a descriptive survey approach. The research sample consisted of 78 respondents selected via accidental sampling. Data analysis was conducted using univariate analysis to describe the characteristics of patient segmentation. The results show that based on demographic segmentation, the majority of patients are aged 45–65 years, have a high school education or equivalent, work as farmers, fishermen, or laborers, and have a sufficient income level. Based on geographic segmentation, the majority of patients reside in the Mamuju City area and occupy their own homes. In psychographic segmentation, most patients have high motivation and perceptions of hospital healthcare services. Meanwhile, based on behavioral segmentation, the majority of patients utilize healthcare facilities when experiencing moderate to severe illness, while for mild illnesses, they tend to self-medicate by purchasing medicine at stalls or pharmacies. Furthermore, patients' frequency of hospital service utilization is relatively high. Based on the research results, it can be concluded that outpatients at Mamuju Regency Hospital are predominantly adults and the elderly, have positive perceptions and motivations about healthcare services, and demonstrate a high level of hospital service utilization. This information can inform the hospital's development of marketing strategies and service development that better align with patient characteristics and needs.